(untitled) (Journal of Philosophy Culture and Political Science, 2024)
There are many people in Kazakhstan with higher education in the field of Islamic teachings. However, for various reasons, the work of these scientists was not properly appreciated and their work was not disclosed. To solve this problem, we tried to determine the place of the Kazakh scientist Shakarim Kudaiberdievich in the Islamic teaching and the importance of his works. The article contains research and information related to the work of Shakarim Kudaiberdiuly "The Muslim Book". The author describes the linguistic and stylistic features of the work, the methods and techniques that the scientist followed when writing. We are talking about the difference between Labor and other similar labor. The structure of sentences that take place inside the work is analyzed. In the course of the article, using a comparative method, the unsolved points related to the title of the work "The Muslim Book" were considered. Using the methods of thematic and textual comparison, the stylistic and content features of this work were determined. Using the method of historical comparison, the importance of the work before the Kazakh people was studied. Keywords: Muslim, linguistic, thematic, textual, features.